THE USE OF HEAT PUMPS IN COMBINED HEATING SYSTEMS FOR URBAN INFRASTRUCTURE - Kunytskyi , M.O. (Municipal economy of cities. Series: «Economy science», 2025)
The article "The use of heat pumps in combined heating systems for urban infrastructure" delves into the potential of integrating heat pumps into modern urban heating systems, with a focus on energy efficiency and environmental sustainability. As urban areas expand and energy consumption continues to rise, the integration of heat pumps presents a promising solution to address both environmental and economic challenges. The introduction emphasizes the growing demand for energy-saving technologies, underscoring the need to reduce environmental impacts associated with traditional heating systems. Keywords such as heat pumps, combined heating systems, energy efficiency, and environmental sustainability are central to the discussion. The relevance of the topic is particularly justified by the increasing costs of traditional energy sources, which are often based on fossil fuels. As global concerns about climate change grow, cities are under pressure to reduce greenhouse gas emissions, which are a significant byproduct of conventional heating methods. The adoption of more sustainable technologies like heat pumps is critical to reducing urban areas’ carbon footprints. The problem statement in the article highlights the excessive energy consumption of conventional systems, as well as their significant contribution to greenhouse gas emissions. By transitioning to heat pumps, cities can not only address these environmental concerns but also ensure a more sustainable and energy-efficient future. The section on the analysis of studies and publications reviews the advantages and challenges of implementing heat pumps in urban environments. One of the key advantages of heat pumps is their ability to harness renewable energy from the environment, such as air, water, or the ground, to generate heating and cooling. This process drastically reduces reliance on fossil fuels and cuts down on emissions. However, several challenges are identified, including the high upfront costs of installation and the modernization of existing heating networks to accommodate these systems. Moreover, there is limited long-term data on the operational efficiency of heat pumps in urban settings, making it difficult to predict their performance over time in various urban climates and infrastructure types. The research aims to provide recommendations for the adoption of heat pumps in urban conditions. The tasks outlined include performing energy efficiency analyses to determine the optimal systems for different types of urban environments. Additionally, the research will explore integration schemes that combine heat pumps with existing heating infrastructure, as well as how to incorporate other renewable energy sources such as solar and wind to enhance overall system efficiency. The main body of the article elaborates on the technical aspects of heat pump operations. Heat pumps work by transferring heat from one location to another, typically from the ground or air to a building, which makes them highly energy-efficient. Their ability to both heat and cool spaces makes them versatile for year-round use in urban infrastructures. The economic feasibility of implementing heat pumps is also addressed. While initial installation costs may be high, the long-term savings on energy bills, coupled with the environmental benefits, make heat pumps a viable option for cities looking to reduce their energy costs and carbon emissions. Finally, the conclusions underscore the promising nature of heat pumps as a solution for urban heating and cooling needs. However, the article stresses the necessity of significant investments in both technology and infrastructure to ensure the successful integration of heat pumps into urban systems. The adaptation of existing heating networks, retrofitting older buildings, and overcoming technological limitations are key challenges that need to be addressed. In summary, the article suggests that while heat pumps offer a promising future for urban infrastructure, they require careful planning, significant investments, and continued research to fully realize their potential for long-term environmental and economic sustainability.